2011
DOI: 10.1080/09593330.2010.512925
|View full text |Cite
|
Sign up to set email alerts
|

Removal and recovery of nutrients as struvite from anaerobic digestion residues of poultry manure

Abstract: The removal and the recovery of nutrients, namely nitrogen (N) and phosphorus (P) from anaerobically digested and solid-liquid separated manure effluents via struvite precipitation were investigated. Both the liquid and the solid phases of the poultry manure digester effluent were subjected to struvite precipitation experiments. The Mg:N:P molar ratio of 1:1:1 in the liquid phase resulted in an average NH4-N removal efficiency of 86.4%, which increased to 97.4% by adjusting the Mg:N:P ratio to 1.5:1:1. The aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 38 publications
1
43
2
Order By: Relevance
“…Yilmazel and Demirer (2011) showed that acidification of the solid fraction of AD effluent produced a phosphorus enriched solution. Yilmazel and Demirer (2011) attained nearly complete phosphorus (99.6-100%) and partial NH 4 -N (3.3-65.6%) recoveries from the phosphorus enriched solution in an optimized fluidized-bed reactor (Yilmazel and Demirer, 2011). To release phosphorus from calcium phosphates in struvite reactors, added EDTA as a chelating agent.…”
Section: Struvite Crystallizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Yilmazel and Demirer (2011) showed that acidification of the solid fraction of AD effluent produced a phosphorus enriched solution. Yilmazel and Demirer (2011) attained nearly complete phosphorus (99.6-100%) and partial NH 4 -N (3.3-65.6%) recoveries from the phosphorus enriched solution in an optimized fluidized-bed reactor (Yilmazel and Demirer, 2011). To release phosphorus from calcium phosphates in struvite reactors, added EDTA as a chelating agent.…”
Section: Struvite Crystallizationmentioning
confidence: 99%
“…The composition of hydroxyapatite is similar to phosphate rocks, indicating it could be integrated into existing fertilizer manufacturing (Bellier et al, 2006). The use of acidification as pretreatment (Yilmazel and Demirer, 2011) and low cost magnesium inputs (Lahav et al, 2013) could improve the cost-effectiveness of struvite crystallization. Future investigations should evaluate struvite crystallization from AD effluent at larger scale and conduct economic analyses for feasibility assessment for both centralized and farm-scale AD systems.…”
Section: Struvite Crystallizationmentioning
confidence: 99%
“…In many cases, particularly those where animal and agricultural waste is the main source of N and P, Mg must be supplemented into the system to promote crystallization. In recent years, struvite recovery has been implemented in the treatment of a variety of wastewater sources, including landfill leachate [85], anaerobic digester effluent [86], as well as swine [87,88], poultry [89], and fertilizer wastewater [90•]. In all cases, after the introduction of Mg, struvite recovery was shown to be between 85 and 97 %.…”
Section: Chemical Precipitationmentioning
confidence: 99%
“…Poultry manure contains a high fraction of biodegradable organic matter and therefore their disposal without treatment causes adverse environmental impacts (Ogunwande et al, 2008). Among the different methods that have been used to treat poultry wastes, anaerobic digestion has been recommended by many authors (Ardic and Taner, 2005;Yilmazel and Demirer, 2011). Anaerobic digestion is a widely applied method in which anaerobic bacteria and archaea degrade complex organic material to biogas (Angelidaki et al, 2011).…”
mentioning
confidence: 99%